Analyzing the Evolution of Nepal's Tourism in 2022: Insights and Future Perspectives - Sharma, Laxmi Kanta; Paudel, Vishal (Cognition, 2024)
This paper focuses into Nepal's internal aviation and tourism industries, underlining the essentiality of strategic planning. It investigates how Nepal's tourism sector has adapted to the global repercussions of COVID-19 and identifies successful strategies to increase tourism revenue following the pandemic. Through the application of both descriptive and inferential statistics, this research analyses data and visually conveys its conclusions. It emphasizes the importance of tailor-made marketing and promotional approaches designed for particular market segments and to exploit local strengths. The document evaluates recovery tactics post-COVID-19, the role of domestic tourism, and the need for upgrades in infrastructure and policies to foster the sustainable development of tourism in Nepal. The necessity for a cohesive approach among federal, provincial, and local governments to facilitate the proper allocation of resources and the execution of tourism initiatives is strongly advocated. The expansion of tourism-related infrastructure, including hotels with high star ratings and improved transport systems, is highlighted as a fundamental factor in supporting the surge of tourists to Nepal. The paper postulates that reinforcing economic development through policies favorable to the tourism industry will have a beneficial impact on international tourism. It urges a policy shift towards the improvement of tourism infrastructure and the adoption of technological innovations in its management.